TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA KINERJA PERUSAHAAN: PERAN PEMODERASI KEPEMILIKAN PEMERINTAH - Tri Yuli Tiastuti Susanti; Ardi Paminto (Universitas Ahmad Dahlan, 2022)
This study aims to obtain empirical evidence regarding the impact of independent variables namely corporate social responsibility and state as moderating variables on firm performance. This study analyzes using a sample of 9 companies in the construction sub-sector listed on the Indonesia Stock Exchange for the period 2013-2018 using the purposive sampling technique. The tools used in this research are panel data regression and descriptive statistics. The results of the study show corporate social responsibility has positive effect but no significant on firm performance and state does not moderate the effect of corporate social responsibility on firm performanceThis study aims to obtain empirical evidence regarding the impact of independent variables namely corporate social responsibility and state as moderating variables on firm performance. This study analyzes using a sample of 9 companies in the construction sub-sector listed on the Indonesia Stock Exchange for the period 2013-2018 using the purposive sampling technique. The tools used in this research are panel data regression and descriptive statistics. The results of the study show corporate social responsibility has positive effect but no significant on firm performance and state does not moderate the effect of corporate social responsibility on firm performance.